Retrievable Inferior Vena Cava Filters for Venous Thromboembolism. (22nd April 2013) - Ni, Han; Win, Lei Lei
Abstract : Inferior vena cava (IVC) filters are used as an alternative to anticoagulants for prevention of fatal pulmonary embolism (PE) in venous thromboembolic disorders. Retrievable IVC filters have become an increasingly attractive option due to the long-term risks of permanent filter placement. These devices are shown to be technically feasible in insertion and retrieval percutaneously while providing protection from PE. Nevertheless, there are complications and failed retrievals with these retrievable filters. The aim of the paper is to review the retrievable filters and their efficacy, safety, and retrievability.